A Functional Approach to the Legal Review of Autonomous Weapon Systems - Copeland, Damian, (Human Rights and Humanitarian Law E-Books Online, Collection 2024., 2025)
Autonomous Weapon Systems (AWS) are no longer limited to science fiction. Conflicts in the Ukraine and Gaza demonstrate an increased trend toward the use of autonomy in the use of force in armed conflict. This book analyses the art 36 legal review obligation and assesses how states can determine the legality of AWS. It proposes a new 'functional' approach to legal review that considers both weapons law and targeting rules engaged by the autonomous functionality.